Ecological Water Demand Calculation with the Consideration of the Health of Fish Spawning Ground——A Case Study of Dongta Spawning Ground in Xijiang River - ZHOU Huabin; YU Chunxue; SU Meirong (Renmin Zhujiang)
The spawning ground is a sensitive place in the fish habitat. It has specialhydrological and hydrodynamic characteristics and has important ecological significance for thenatural reproduction of fish. Calculation of ecological water demand for the natural reproductionof four major Chinese carps and ensuring of the water demand for domestic fish reproduction areeffective method to effectively alleviate the decline trend of domestic fish resources. Taking theDongta spawning ground in the Xijiang River Basin as the study area and four major Chinese carpsas the target species for the first time, this paper constructs the related suitability curve forthe hydrodynamic characteristic index, simulates the effects of factors such as flow velocity andwater depth on fish spawning grounds at different flow conditions by a two-dimensional riverhydrodynamic model, River2D, establishes the relationship between the flow conditions and weightedusable area (WUA) of four major Chinese carps habitats to determine the ecological water demand inthe study area. The results show that based on the simulation results of twenty flow conditions (1000~20 000 m3/s), the maximum WUA of the Dongta spawning ground is 101 935.48 m2, and theecological water demand corresponding to the WUA is 10 277.54~12 546.61 m3/s, which can be used asthe peak ecological water demand during the spawning period of the four major Chinese carps. Basedon the simulation results of historical monthly average flow conditions, the corresponding flowsof the minimum WUA in the Dongta spawning ground from January to December are 1 339.67, 1 256.53,1 361.93, 2 126.09, 4 057.10, 6 202.66, 6 734.19,5 316.12, 3 092.66, 1 680.32, 1 234.40, 1 168.32m3/s, which are the minimum ecological water demand to maintain the function of Dongta spawningground. Determining the ecological water demand of the river based on the health of the spawninggrounds of the four major Chinese carps is conducive to the improvement of fish resources, and isof important ecological significance in maintaining biodiversity and even the entire ecosystem.